KINERJA PENYULUH PERTANIAN PADA BALAI PENYULUHAN PERTANIAN PERIKANAN DAN KEHUTANAN KECAMATAN SINIU KABUPATEN PARIGI MOUTONG - Maryam, Sitti (Katalogis, 2018)
The problem in this research is the level of performance of agricultural extension is not maximized therefore the study aims to determine the results of the performance of the agricultural extension at the Institute of Agriculture Fisheries and Forestry Extension Siniu District of Parigi Moutong district. In this study used qualitative research methods. Where the results of such work can be related to the quality, quantity, effectiveness, timeliness and independence that emphasize the final result (come out) obtained in carrying out the work as agricultural extension activities. The fifth element of the appearance of the above characteristics related to the field of agricultural extension tasks mostly been shown in the implementation of their respective duties agricultural extension. But both elements are: quality and timeliness is not optimal implemented by most agricultural extension. Informants in this study were 8 people. Data analysis techniques as usual qualitative research, namely data reduction, data presentation, and conclusion. Results showed the five elements relative performance has been carried out, although there are two elements is still not optimal to run. This means we need a policy discipline lead in promoting agricultural extension in order to carry out tasks that emphasize on enhancing the quality of work extension, as well as in performing the task should be timely.